Basin futures : water reform in the Murray-Darling basin - Connell, Daniel; Grafton, R. Quentin, 1962- (ANU E Press, 2011)
"This unique book brings together 27 chapters from some of the world's leading practitioners and experts on environmental water, communities, law, economics and governance. Its goal is to understand the many dimensions of water in the Murray- Darling Basin and provide guidance about how to implement a water management plan that addresses the needs of communities, the economy and the environment."--Publisher's description